2022
DOI: 10.3389/fcell.2022.840759
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Analysis of the Differential Expression and Prognostic Value of Histone Deacetylases in Glioma

Abstract: Gliomas are the most common and aggressive malignancies of the central nervous system. Histone deacetylases (HDACs) are important targets in cancer treatment. They regulate complex cellular mechanisms that influence tumor biology and immunogenicity. However, little is known about the function of HDACs in glioma. The Oncomine, Human Protein Atlas, Gene Expression Profiling Interactive Analysis, Broad Institute Cancer Cell Line Encyclopedia, Chinese Glioma Genome Atlas, OmicShare, cBioPortal, GeneMANIA, STRING, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 80 publications
0
9
0
Order By: Relevance
“…TIMER Database Analysis. For the inclusive analysis of the TIICs, such as B cells, neutrophils, dendritic cells, CD4 + T cells, CD8 + T cells, and macrophages, the TIMER database (https://cistrome.shinyapps.io/timer/) was utilized by using the RNA-seq expression profile data [21,22]. We used the "Gene" module plots to evaluate the link of TTC7B expression and immune infiltrate level with tumor purity.…”
Section: Cibersort Analysismentioning
confidence: 99%
“…TIMER Database Analysis. For the inclusive analysis of the TIICs, such as B cells, neutrophils, dendritic cells, CD4 + T cells, CD8 + T cells, and macrophages, the TIMER database (https://cistrome.shinyapps.io/timer/) was utilized by using the RNA-seq expression profile data [21,22]. We used the "Gene" module plots to evaluate the link of TTC7B expression and immune infiltrate level with tumor purity.…”
Section: Cibersort Analysismentioning
confidence: 99%
“…Previous research demonstrated an elevated HDAC3 protein level in patients with glioma, indicating its potential role in glioma diagnosis and treatment ( 20 ). HDAC1, 4, 5, 8, 9, and 10 proteins have also been shown to be elevated in glioma ( 21 - 23 ). Furthermore, the combination of RGFP109, an inhibitor of HDAC3, and temozolomide (TMZ) was reported to be a promising therapeutic option for patients with TMZ-resistant GBM ( 24 ).…”
Section: Resultsmentioning
confidence: 99%
“…In our study, the NCAPG2 and BAZ1B genes were positively related to NUP205 and have been reported as oncogenes for glioma. In addition, HDAC11 , which was negatively correlated with the expression of NUP205 , was found to have low expression in glioma tissue and was associated with a better prognosis in glioma patients ( 37 ). Interestingly, AVPI1 , FKBP8 , and ALDH2 , which were most negatively correlated with NUP205 in LGG, were all reported to be tumor suppressor genes in cancer ( 36 , 38 , 39 ).…”
Section: Discussionmentioning
confidence: 99%